Sedimentology and Society - Owen, Amanda; Andrew Clare, Michael; Mauz, Barbara (Frontiers Media SA, 2020)
Understanding the societal impacts of, and improving resilience in response to Earth surface processes requires advancing and applying process sedimentology research in a wide range of environments. This means that these are exciting times for sedimentologists, as we have a growing range of tools, approaches and expertise to tackle some of the key challenges that face society; such as better understanding natural hazards, forecasting fluxes of contaminants through sediment transport pathways, and understanding the long-term transfer and storage of carbon. For instance, sedimentology has a key role in improving our understanding of both the frequency and impact of a wide range of geohazards that both directly and indirectly impact global communities, especially in more vulnerable Developing Countries. In particular, the links between cascades of hazards, and their response to anthropogenic changes are important but poorly understood. Recent advances in monitoring and analytical methods, as well as adaption of existing approaches, provide the opportunity to fill these outstanding knowledge gaps, as well as gaps in other areas, such as the dispersal of pollutants (e.g. microplastics, pesticides) in the natural environment. Understanding pollutant, and other important particulate (e.g. organic carbon) transport pathways, and their ultimate fates, requires detailed characterisation of the sedimentary processes within and between environments, over a wide range of timescales.